Cardiac involvement in patients of systemic sclerosis - Ahmad Qazi; Shah Iffat; Nauman Qazi; Sameem Farah; Kamili M (Wolters Kluwer Medknow Publications, 2008)
Background: Systemic sclerosis is a multi-systemic autoimmune disorder. Cardiac involvement by the disease, although not included in the diagnostic criteria, may be seen either clinically, histologically or may be revealed by various investigative modalities. Purpose: To see the profile of cardiac involvement in patients of systemic sclerosis. Materials and Methods: Forty-seven patients of systemic sclerosis were included in the study. After taking a complete history and doing a detailed physical examination, the patients were submitted to electrocardiogram ECG (all leads), echocardiography and x-ray chest. Furst′s organ indices scoring system for cardiac involvement was followed. Findings: Forty-seven patients of systemic sclerosis were included in the study. Five females gave a history of palpitations. A loud pulmonic heart sound was heard in 1. Arrhythmias were observed in 5 patients. Significantly, echocardiography revealed valvular involvement in 5 patients. Left ventricular hypertrophy was seen in 2 patients. Conclusions: In our patients, cardiac involvement was rare. In contrast to other studies, valvular involvement was a prominent feature. Limitations: Complete evaluation for arrhythmias with 24-h Holter monitor was not used